2016
DOI: 10.1590/s0100-204x2016000800002
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade de soja em consequência do atraso da colheita e de condições ambientais

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito do atraso da colheita sobre umidade dos grãos, massa de mil grãos e produtividade da soja, assim como identificar as variáveis agrometeorológicas mais importantes durante o período pré-colheita e propor algoritmos empíricos para a estimativa das perdas de produtividade. Os experimentos foram realizados em Castro, PR, e Itaberá, SP, nas safras de 2011/2012 a 2013/2014, da cultivar de soja 'NA5909RG', em sete ambientes. Os tratamentos consistiram de oito mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
1
7
0
5
Order By: Relevance
“…Com a finalidade de otimizar o processo de colheita, a escolha da cultivar torna-se uma ferramenta eficiente, garantindo altas produtividades (Amorim et al, 2011). A produtividade e seus componentes e as características agronômicas são atributos genéticos, porém fortemente influenciados pelas condições climáticas (Tsukahara et al, 2016).…”
Section: Introductionunclassified
“…Com a finalidade de otimizar o processo de colheita, a escolha da cultivar torna-se uma ferramenta eficiente, garantindo altas produtividades (Amorim et al, 2011). A produtividade e seus componentes e as características agronômicas são atributos genéticos, porém fortemente influenciados pelas condições climáticas (Tsukahara et al, 2016).…”
Section: Introductionunclassified
“…In a study on the behavior of fully mature soybean seeds under field conditions, Tsukahara et al (2016) verified that the seed moisture is directly impacted by the number of days with precipitation levels equal to or above 3 mm, within the span between the beginning of the R8.2 stage and the harvest. They also concluded that the most substantial productivity losses happen in environments with high rainfall frequency, hot temperatures, and intense sunlight incidence.…”
Section: Resultsmentioning
confidence: 88%
“…This condition intensifies seed deterioration and facilitates the penetration of pathogens, as the inner tissues become more exposed. Therefore, it potentially reduces overall productivity (Marcandalli et al, 2011;Pádua et al, 2014;Tsukahara et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The soil was classified as typic dystroferric Red Latosol and the climate, according to Köppen's classification, as Cfa, with hot summer without dry season (Kuinchtner & Buriol, 2001). Ten days prior to sowing, soil analysis was performed (Tedesco et al,1995) and, on the average of the years, the following characteristics were identified: i) soybean/wheat system (pH = 6.1, P = 49.1 mg dm -3 , K = 424 mg dm -3 , OM = 30 g kg -1 , Al = 0 cmol c dm -3 , Ca = 6.3 cmol c dm -3 and Mg = 2.5 cmol c dm -3 ) and; ii) maize/ wheat system (pH = 6.5; P = 23.6 mg dm -3 ; K = 295 mg dm -3 , OM = 29 g kg -1 , Al = 0 cmol c dm -3 , Ca = 6.8 cmol c dm -3 and Mg = 3.1 cmol c dm -3 ). Sowing was made using a seeder-fertilizer machine to compose the plots with five 5-m-long rows spaced by 0.20 m, forming the experimental unit with 5 m 2 .…”
Section: Methodsmentioning
confidence: 99%